Anaesthesia for surgical decompression of pott's spine in second trimester of pregnancy with lung isolation technique: An interesting case report - Veena Ganeriwal; Paulomi Dey; Sukanya Khan (Wolters Kluwer Medknow Publications, 2018)
Spinal tuberculosis (Pott's disease) during pregnancy is reported to be rare and can be associated with destruction of the intervertebral disc and adjacent vertebrae that can lead to cord compression and thereby paraplegia or quadriplegia. Awareness of signs and suitable investigations may be delayed due to pregnancy, as patient and clinician may attribute these to the gravid state. The existing literature is limited and inconclusive regarding general anaesthesia using double-lumen endotracheal tube with lung isolation technique in the surgical decompression of spinal tuberculosis during pregnancy. We describe the successful anaesthesia management of a 26-week primigravida with 3rd to 5th thoracic spine (T3-T5) tuberculosis with paraparesis who underwent T4 corpectomy with T3-T5 fusion through transaxillary transthoracic approach.